Induction of cytotoxic T cell precursors in vivo. Role of T helper cells (The Rockefeller University Press, 1983)
Strain AS rats respond with two populations of cytotoxic T lymphocytes to stimulation in vitro by the major histocompatibility complex (MHC)- incompatible strain HL rat tumor (HL-A2T2). One is specific for MHC alloantigens present on both HL-A2T2 and normal HL targets, the other is tumor specific. The activation of these killer cells requires helper T lymphocytes. The tumor-specific helper cells depend on syngeneic radioresistant accessory cells to present the tumor antigens in an immunogenic form. The appropriate helper-accessory cell interaction results in the production of soluble factors which then induce the maturation of precursor cells into effective killer cells. Studies with a procedure for inducing negative selection of T cells in vivo showed that short-term exposure to HL-A2T2 tumor induced selection only for TH but not cytotoxic T lymphocyte precursors (CTLp). Simultaneous injection of supernatants from concanavalin A-activated spleen cell cultures, however, did produce selection of CTLp. These and other findings suggest that under normal circumstances in vivo, both signals (recognition of antigen and acceptance of maturation factors) are provided in the vicinity of an antigen presenting macrophage-like accessory cell.